Survive in the woods - Bowman, Chris, 1990- (2017)
"Amazing photography accompanies engaging information about how to survive in the woods. The combination of high-interest subject matter and light text is intended for students in grades 3 through 7"--
Alone in the woods -- Surviving in the woods -- Finding shelter -- Making fire -- Drinking water -- Eating food -- Avoiding animals.
Includes bibliographical references and index.
Grades 3-7
Keywords: Wilderness survival -- Juvenile literature